A case report of occurrence of severe alopecia areata as post-COVID-19 complication: Post-COVID Alopecia Areata - Saeed, Sana (Journal of Pakistan Association of Dermatologists, 2023)
COVID-19 has been markedly affecting the lives of individuals in various ways from past two years. Post COVID-19 complications are among those which have rendered patients more vulnerable to secondary diseases. Hyperactive immune system is one of the post-COVID complications. This has led to emergence of all forms of alopecia in patients who suffered from COVID-19. A 33-year-old female is experiencing severe alopecia areata as a post-COVID complication with aberrant response towards treatments from past 9 months. Topical minoxidil 5% and tacrolimus 0.1% along with scalp platelets-rich-plasma (PRP) with micro-needling has been proven successful in regrowth after two months of treatment. Although reoccurrence of few bald patches has been observed.